ANALISIS KONTRIBUSI PENDAPATAN ASLI DAERAH (PAD) DAN DANA PERIMBANGAN TERHADAP BELANJA PEMERINTAH KABUPATEN MUSI BANYUASIN - Hasyunah . (JURNAL KOMPETITIF, 2014)
ABSTRACTÃ‚Â This study aimed to determine the effect of region income of Local Government Expenditures in Banyuasin, to determine the effect of Revenue Sharing on Local Government Expenditures Banyuasin and to know the effect of Local Revenue Equalization Fund of Local Government Expenditures in Banyuasin. Regional Revenue Contribution to the shopping area is still very low at an average of 23.4% with an average increase of 0.11% per year. While most of the district government expenditures amounted to 93.49% in Banyuasin funds come from fund balance. While the balance fund contributions to local spending is as high as an average of 93.49% with a decrease of 1.58% per year. Trend region income increasing and balancing the increasingly indicate that the development of independence in Banyuasin County Government for its budget each year has increased. This indicates that the District Government has been trying Banyuasin independent in managing the financial area and try to be autonomous in accordance with the goals you want to target in the regional autonomy that is the achievement of fiscal autonomy of a region. Also in Banyuasin regency government has been trying to reduce its dependence on transfers from the central / provincial financial manage their areas and strive to create and explore more potential derived from its own country.Keywords: Contributions, Fund Balance and Expenditure